2000
DOI: 10.1088/0957-0233/11/11/305
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic evaluation of semi-solid metals during processing

Abstract: Ultrasonic velocity and attenuation measurements for three different semi-solid (SS) aluminum (Al) alloy billets (A356, A357 and 86S) and one dendritic sample (A356) were performed in the temperature range between room temperature and ~575 °C using a non-contact laser-ultrasonic technique. It was found that there are measurable differences in ultrasonic velocity and attenuation between SS and dendritic samples and these differences are larger as the temperature becomes closer to the complete melt state. In a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Jen and co-workers [23], [24], [25], [26] have tried to limit the number of modes traveling in a thin bar by adding an attenuative cladding on the outside of the bar, the bar usually being tapered. This is essentially an attempt to remove the effects of the waveguide boundaries by reducing the amplitude of reflections from the surface.…”
mentioning
confidence: 99%
“…Jen and co-workers [23], [24], [25], [26] have tried to limit the number of modes traveling in a thin bar by adding an attenuative cladding on the outside of the bar, the bar usually being tapered. This is essentially an attempt to remove the effects of the waveguide boundaries by reducing the amplitude of reflections from the surface.…”
mentioning
confidence: 99%
“…From [22], the ultrasonic longitudinal wave velocity in the Al decreases about 1.1 (m/s)/ • C between room temperature and 500 • C at 10 MHz. According to our experience, the shear wave velocity decreases similarly but with a slightly higher slope than the longitudinal wave velocity.…”
Section: Discussionmentioning
confidence: 91%
“…According to our experience, the shear wave velocity decreases similarly but with a slightly higher slope than the longitudinal wave velocity. The ultrasonic attenuation in the Al increases about 0.01 dB/cm between room temperature and 500 • C at 10 MHz [22]. In our experiments, because the echoes reflected from the Al probing end/sample interface and those from the other side of the sample are used to evaluate the velocity and attenuation in the sample, the temperature effects on the velocity and attenuation in the Al rod itself are not of a concern.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies to evaluate the semi-solid state during processing have been reported. Ultrasonic, for example, is applied to monitor the condition of semi-solid metals during processing [ 26 ]. A process using acoustic emission to determine the semi-solid condition by induction heating [ 27 ] is also reported.…”
Section: Operation Of Thixoforming Systemmentioning
confidence: 99%